Study of the Optimum Arrangement of Spherical Particles in Containers Having Different Cross Section Shapes - Slíva, Aleš; Brázda, Robert; Procházka, Aleš; Martynková, Gražyna Simha; Barabaszová, Karla ˇech (Journal of nanoscience and nanotechnology, 2019)
Fluidized bed porosity ɛ is a primary property of fluidized systems when determining the minimum floating velocity. The air flow rate in the fluidized bed (or in the fluid layer of the material) increases with diminishing bed porosity. This paper is devoted to porosity calculations for a fluidized bed consisting of spherical particles having different diameters (2, 4, 6, 8, 10 mm) and in differently shaped polygonal fluidized bed cells possessing different characteristic particle floating velocities. For testing purposes, porosity was experimentally measured and subsequently modelled by simulation using the Rocky code. Cells with regular triangular, tetragonal (square-shaped), pentagonal, hexagonal, heptagonal and circular cross sections were used for the experiment. All the cells possessed the same cross-section area S = 1256 mm². The weight of the spherical particle batch in the experiments was constant, 2 kg, for all of the fluidized bed cell cross section shapes described above.